Effective Newborn Screening for Type 1 and 3 Primary Hyperoxaluria - Bernd Hoppe; Cristina Martin-Higueras; Lodovica Borghese; Sophie Kaspar; Björn Reusch; Bodo B. Beck; Adam Walli; Ella Janzen; Sebastian Hegert; Nils Janzen; Katharina Hohenfellner (Kidney International Reports)
Introduction: Newborn screening (NBS) programs for a defined set of eligible diseases have been enormously successful, but genomic NBS allowing for detection of additional treatable disorders has not been broadly implemented. All 3 types of primary hyperoxaluria (PH1–3) are rare autosomal recessive diseases caused by distinct defects of glyoxylate metabolism that are diagnosed genetically with certainty. Early diagnosis and treatment are mandatory to avoid renal failure or sequalae associated with persistent hyperoxaluria. Methods: This prospective pilot study was undertaken within the framework of the German NBS. DNA samples extracted from dried blood spot cards were screened by multiplex polymerase chain reaction (PCR) for the 2 most prevalent variants: AGXT c.508G>A (PH1) and HOGA1 c.700 + 5G>T (PH3). Heterozygous AGXT/HOGA1 carriers received repeated spot urine analyses and, in case of persistent hyperoxaluria, complete Sanger sequencing of AGXT and HOGA1 genes, respectively. Results: Between March 15, 2022 and June 30, 2023, additional screening for PH1 and PH3 was performed in 77,199 out of 222,638 newborns included in the regular NBS program. No homozygous individuals, but 274 potential carriers for the AGXT mistargeting and 287 potential carriers for the HOGA1 splice variant were identified. Further workup revealed 2 already symptomatic compound heterozygous infants, 1 with PH1 (genotype c.508G>A; c.33delC) and 1 with PH3 (genotype: c.700 + 5G>T; c.134C>G). A second symptomatic patient with PH1 (father of an identified carrier; genotype: c.508G>A; c.508G>A) was uncovered via family history. Conclusion: This pilot study demonstrates the efficacy of a genomic neonatal screening program for PH even in relatively small cohorts.